Geomatica per l’informazione climatica locale e per i servizi climatici: un caso di studio per l’area mediterranea. - Caiaffa, Emanuela; La Porta, Luigi; Pollino, Maurizio (GEOmedia, 2016)
The present paper describes a methodology developed for overcoming problems linked to the climate changes science in order to make it effectively accessible to end users: stakeholders, policy makers, citizens. In today's scientific approach, communication on climatic information and on climatic changes condition, has to be clear, accessible and perceptive to everyone, to definitely arise the right interest on such problem. Results coming from climatic changes Research and Development projects, in addition to being accepted by policymakers, that have to take future decisions and practical actions to mitigate their possible negative effects, must also be recognized and believed by ordinary citizens that have to understand and accept restrictions, for example in energy consumptions, potentially affecting their habit of life. Accordingly, it will be necessary to regenerate policy-making world so as to make it more direct and potentially open to networking interactive communication tools.